2003
DOI: 10.1021/jp0276808
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Dechlorination of Trichlorobenzene on Oxide Surfaces

Abstract: 1,2,3-Trichlorobenzene (TCB) was ground with calcium oxide (CaO) powder in air with a planetary ball mill. A mechanochemical reaction was induced, resulting in the decomposition of TCB through dechlorination from the benzene nucleus. The mechanochemical dechlorination was monitored by a suite of analytical methods including X-ray diffraction (XRD), thermogravimetry (TG), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, electron spin resonance (ESR), gas chromatography/mass spectrometry (GC/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 41 publications
5
47
0
Order By: Relevance
“…These complex and poorly understood surfaces usually lead to a variety of chemical interaction pathways. Tanaka (2003) reported that the mechanochemical decomposition of trichlorobenzene on CaO was not dehydrochlorination but dechlorination; similar conclusion was also drawn by Krishnamoorthy (2000). However, the oxidation process also existed during the decomposition of chlorinated aromatic compounds.…”
Section: Decomposition Mechanisms and Pathways Of Hcbmentioning
confidence: 52%
“…These complex and poorly understood surfaces usually lead to a variety of chemical interaction pathways. Tanaka (2003) reported that the mechanochemical decomposition of trichlorobenzene on CaO was not dehydrochlorination but dechlorination; similar conclusion was also drawn by Krishnamoorthy (2000). However, the oxidation process also existed during the decomposition of chlorinated aromatic compounds.…”
Section: Decomposition Mechanisms and Pathways Of Hcbmentioning
confidence: 52%
“…Other study also presented similar results. Yasumitsu et al [30] used calcium oxide as additive to destruct 1,2,3-Trichlorobenzene (TCB) by ball milling, and found that the final products contained some minor methane and ethane except carbon after 360 min milling. Loiselle et al [21] also detect methane and ethane in the end products during the process of mechanochemical treatment of chlorobenzenes.…”
Section: Mechanistic Interpretationmentioning
confidence: 99%
“…[1,2,3,4] Ball mills provide one of the most common tools for mechanical stimulation of solid state processes such as phase transitions, [5,6,7] solid-solid reactions [8,9,10,11,12] decompositions, [13,14] as well as degradation [15,16,17] and amorphization [18] of polymers. Ball mills are capable of producing high strain fields that allow for initiating the aforementioned processes without heating.…”
Section: Statement Of the Problem Studiedmentioning
confidence: 99%